Development of Powtoon Learning Media for Student Learning Activities in Theme 2 Clean Air For Health Class V SDN 064954 Medan Amplas - Amaliya, Putri; Landong, Ahmad (Universitas Trunojoyo Madura, 2023)
This study aims to: (1) develop Powtoon learning media for student learning activities on theme 2 clean air for health for grade V SD, (2) determine the feasibility of developing the Powtoon application in SD thematic learning. This research is a type of Research and Development (RD) research with the ADDIE model which includes five steps including: analysis, design, development, implementation, evaluation. The subjects in this study were media expert validators, education practitioners, material experts, namely fifth grade teachers and fifth grade elementary school students. The research instruments used in data collection were questionnaires, observation, and documentation. The results of this study indicate that Powtoon learning media in Thematic Learning Theme 2 Clean Air for Health Class V SD